2022
DOI: 10.3390/agronomy12030697
|View full text |Cite
|
Sign up to set email alerts
|

Soil—Plant Relationships in Soybean Cultivated under Conventional Tillage and Long-Term No-Tillage

Abstract: Soybeans [Glycine max (L.) Merrill] have great economic prominence in the world, and soil management systems can directly interfere with their yield through changes in soil physical-hydric properties. Thus, the aim of this research was to verify the relationship between yield components, physiological traits, root development, and soil physical-hydric properties in soybean yields grown under conventional tillage and no-tillage systems. The experiment was carried out in Botucatu, SP, Brazil, with two treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The higher PR, observed in the sunn hemp rotation system, did not affect the water infiltration in the soil thus contributing to greater water availability to plants. With a greater water supply, the plants did not need to develop roots in depth due to the water supply provided by the system, reducing the energy expenditure with root development and also contributing to the best water content in the plants [ 24 , 38 , 39 ]. Thus, rotation with sunn hemp in long-term NT was characterized as a production system less vulnerable to dry spells and drought.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher PR, observed in the sunn hemp rotation system, did not affect the water infiltration in the soil thus contributing to greater water availability to plants. With a greater water supply, the plants did not need to develop roots in depth due to the water supply provided by the system, reducing the energy expenditure with root development and also contributing to the best water content in the plants [ 24 , 38 , 39 ]. Thus, rotation with sunn hemp in long-term NT was characterized as a production system less vulnerable to dry spells and drought.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the appropriate choice of species to use in a crop rotation system in NT can lead to greater water availability [ 8 , 24 ]. Understanding the dynamics of water in the soil becomes essential for correctly planning agricultural activities, with water being the factor that most affects crop yield [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mondal and Chakraborty, via research with meta-analysis, confirmed that no-tillage practices contribute to soil structural development and an increase in water retention pores, even over a short-term period, however, they did not report the effects of these soil changes Plants 2023, 12, 3762 2 of 17 on the development of agricultural crops. Usually, in CT areas, the soil has a lower rate of water infiltration, lower water storage capacity, and lower water availability to plants, since it is a system with greater vulnerability to crops in periods of heavy rains or drought [6][7][8]. In this management system, the soil is frequently turned, modifying its physical and hydraulic properties in a short time, with the layer being frequently compacted between 0.10 and 0.20 m [9,10].…”
Section: Introductionmentioning
confidence: 99%